The efficacy of PRECEDE-PROCEED model-based interventions on HbA1c and self-management in type 2 diabetes patients: a systematic review and meta-analysis - Yan Tang; Kim Lam Soh; Wan Ying Gan; Junjun Zhou; Kim Geok Soh (BMC Public Health)
Abstract Background Type 2 diabetes is a global public health challenge characterized by high prevalence and poor self-management outcomes. The PRECEDE-PROCEED model is a well-known conceptual widely used to promote health in chronic diseases. This meta-analysis evaluated the efficacy of interventions based on PRECEDE-PROCEED model in reducing Glycated Hemoglobin A1c (HbA1c) and enhancing self-management in patients with type 2 diabetes. Methods Nine online databases—PubMed, Cochrane Library, Embase, PsycINFO, Scopus, CINAHL, Web of Science, CNKI, and WANFANG—were searched from inception to June 2024. Randomized controlled trials (RCTs) and quasi-experimental studies (QESs) were identified using keywords related to the PRECEDE-PROCEED model, type 2 diabetes, and self-management. Review Manager 5.4 was used for meta-analysis and the 95% confidence intervals (CIs) was calculated for standardized mean differences (SMDs) or weighted mean differences (WMDs). Results Fourteen studies (11 RCTs and 3 QESs) involving 2,478 patients met the eligibility criteria. Interventions significantly reduced HbA1c, with progressive improvements over time: WMD = -0.41 (95% CI: -0.58 to -0.24) at 1 month, -0.50 (95% CI: -0.67 to -0.33) at 3 months, and -0.63 (95% CI: -0.93 to -0.33) at 6 months. Significant improvements were also observed in total self-management scores (SMD = 2.53; 95% CI: 1.14to 3.91) and in key PRECEDE-PROCEED model variables, including knowledge, attitudes, self-efficacy, reinforcing, and enabling factors, though high heterogeneity was noted. Conclusions The PRECEDE-PROCEED model is an effective framework for reducing HbA1c and enhancing self-management among patients with type 2 diabetes. Future research should focus on standardizing intervention protocols and developing unified outcome measures to improve reproducibility and cross-study comparability. Trial registration The PROSPERO registration ID is CRD42024600814.